Multi-objective design of industrial symbiosis in palm oil industry - Ng, Rex T.L. (Animo Repository, 2014)
This paper presents a systematic approach for synthesising and designing multiple owners of bioenergy system in palm oil industry. The concept of industrial symbiosis (IS) is adapted to enhance the interaction of processing plants as well as to facilitate processing plants' cooperation. The decision of processing plants' participation in IS system can be affirmed via disjunctive fuzzy optimisation approach based on processing plants' declared economic interests and inherent safety of entire IS system. In cases where the interest (either economic or safety aspects) of any processing plant is not satisfied, that party can elect to withdraw from the IS scheme. The optimum network configuration with the maximum individual economic interests and minimum individual inherent safety is determined prior to the proposed approach. An industrial case study based on palm oil industry is solved to illustrate the proposed approach. © 2014 Elsevier B.V.